Diagnoses and Outcomes of Patients with Suspicion of Acute Coronary Syndrome and Raised High Sensitive Troponin I: A Single Center Study from Pakistan - Kanani, Fatima; Maqsood, Sidra; Wadhwani, Vandana; Zubairy, Maliha; Iftikhar, Imran; Zubairi, Adnan Mustafa (Journal of Laboratory Physicians, 2023)
Objectives Troponins are classically raised in acute coronary syndrome (ACS) although other cardiovascular and non-cardiovascular causes are recognized. We aimed to see the association of high sensitivity (Hs) Troponin I values exceeding the sex-specific 99th percentile upper reference limit (URL) with diagnoses, emergency department (ED) outcomes, 30-day outcomes of admitted patients and predictors of ACS in both genders.Materials and Methods A retrospective study of all patients presenting to the emergency department from January 2019 to April 2021 with suspicion of ACS and Hs-Troponin I values greater than the sex-specific 99th percentile URL.Statistical Analysis SPSS version 24 was used, Pearson's chi-square tests, Fisher's exact test, Kruskal–Wallis test, Mann–Whitney U test, and odds ratios, including the 95% confidence intervals, for each characteristic were used for analysis. A p-value of < 0.05 was considered significant.Results There were a total of 5,982 patients (3,031 males, 2,951 females), out of which 878 patients were admitted under the cardiology specialty. In patients who were admitted to the ward, mortality was higher in females (8.2%) with less than a 10-fold rise in Hs-Troponin I while similar in both genders (7.6%) in patients with Hs-troponin I greater than 10-fold of sex-specific 99th percentile URL. Raised low-density lipoprotein-cholesterol was a significant factor associated with 2.4 times higher odds of ACS.Conclusion Women with Hs-Troponin values up to 10 times the URL, i.e., 15.6–160 ng/L have higher mortality than their male counterparts. LDL-cholesterol is a significant risk factor for ACS which should be controlled for its prevention.
Keywords: acute coronary syndrome; myocardial infarction; non-ST-elevation myocardial infarction (NSTEMI); cardiac troponin; LDL cholesterol; emergency department